From Assertion to Action: Illocutionary Speech Acts in Biden’s Rhetoric of Pandemic Resilience - Galuh Fitriana Sakti; Gunawan Gunawan; David Tombeng; Bayu Andika Prasatyo (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study investigates the strategic deployment of illocutionary speech acts in President Joe Biden's address commemorating the first anniversary of the COVID-19 shutdown. Through a qualitative pragmatic analysis, we examine how presidential rhetoric functions during national crises to inform, reassure, and mobilize public response. The research categorizes utterances from Biden's speech according to Searle's (1969) taxonomy of illocutionary acts: assertives, commissives, directives, expressives, and declaratives. Analysis of the official transcript from the White House website reveals a strategic distribution of speech acts with assertives dominating the discourse, followed by commissives and expressives, directives, and declaratives. This distribution reflects Biden's rhetorical priorities: establishing factual authority through assertives, building trust through balanced commitment (commissives) and emotional connection (expressives), while carefully limiting authoritative commands (directives) and institutional pronouncements (declaratives). The findings demonstrate how presidential crisis communication strategically balances informational transparency with emotional resonance to foster public compliance and national unity. This study contributes to our understanding of political pragmatics by illuminating how speech act distribution serves as a deliberate rhetorical strategy in pandemic discourse, with implications for crisis communication theory and political speech writing practice. Future research should consider analyzing illocutionary acts in a broader range of political speeches across different contexts and cultures to better understand how public figures use language to influence public perception and policy support.